Privacy Preserving Using AES-Mapping in Mix Column Encryption Algorithm: Cloud Approach - Kumari, Anjali; Namdeo, Varsha (International Journal of Computer Sciences and Engineering, 2019)
In this paper we evaluate the efficient, scalable and practical method for privacy-preserving using k-nearest neighbors (KNN) classification method for EMR data. The approach enables performing the widely used k-NN classification method in complex scenarios where none of the parties reveal their information while they can still cooperatively find the nearest matches. To development AES- S.BOX mapping in mix column privacy preserving model used for preserving the privacy of the patients data in a cloud assisted system as the complex information is needed to be maintained confidential and should not be revealed to public users other than the physicians. As we know AES is based on several mathematical perform for security purpose substitutions, permutation and transformation.